Bioplastics and waste management. (August 2018) - Calabrò, Paolo S.; Grosso, Mario
Abstract: Pollution of the marine environment due to plastic materials is one of the most severe environmental problems humanity has to face in the 21st century. The strategy devised until now to address this issue is mainly based on two pillars: (1) increasing the interception of discarded plastic wastes by waste management systems; and (2) substituting the traditional "petro-based" polymers with biodegradable ones. Many issues on the overall sustainability of the second option by the waste management system must still be clarified.